Nilai-Nilai Pendidikan Karakter Dalam Kitab Adab Al-‘Alim Wa Al-Muta’allim dan Relevansinya Terhadap Pendidikan Karakter di Indonesia - Saipullah, Saipullah (Tarbawiyah Jurnal Ilmiah Pendidikan, 2020)
The results of this study concluded that the strengthening of the feeling is more effective than the strengthening of the ratio in self-development. It can be done withthat the values ​​of character education contained in Adab al-‘Alim wa al-Muta‘allim written by KH. Hasyim Asyari are taqwa, loving science, zuhd, discipline, al-qawamiyah, patience, wara’, tawad‘u, hard work/sincerity, loving cleanliness, democracy, affection, communication/ frienkedship, righteousness, social care, and gratitude. These 17 values ​​are in accordance with character education in Indonesia. So that it can be interpreted that the values are proven to form a good disciple (santri) and support effective teaching and learning activities. The primary source of this study is Adab al-‘Alim wa al-Muta‘allim written by KH. Hasyim Asyari. While secondary data are references related to character education in the form of books, magazines, journals and other references relevant to this research. This research is library research. The data obtained were analyzed by descriptive-analysis approach that is by describing the book Adab al-‘Alim wa al-Muta‘allim withsocial history analysis in character education, then analyzed by conducting in-depth study about character education values and their relevance to character education in Indonesia.